Upholding the existence of gamad dance art and educational programs: Cultural signifiances, challenges, and presevation efforts - Yolanda, Elsa; Agustina (Indonesian Research Journal in Education |IRJE|, 2025)
This research aimed to describe and analyze the existence of Gamad dance art in Kota Mukomuko district, Mukomuko Regency, Bengkulu Province. It used qualitative research with data collection techniques consisting of interviews, observation, and documentation. The research object was the Gamad dance art in Mukomuko. The research site was at the Gamad art studio in Ujung Padang Village, Kota Mukomuko. The research showed that the Gamad dance performance had even fewer dancers. Some dances contained in the Gamad dance art were Sempaya, Bercerai Kasih, Pinang Island or Payung dance, Cis Marilom, Sakora, and others. The dance movements use Malay movements that are dominant in footwork, steps, hand swings, and silat movements. The costumes and make-up used by female dancers are baju kurung or long kebaya, songket skirts, headscarves, and beautiful make-up. The male costume uses a Malay suit with a side of songket cloth and a peci. Dance properties include scarves, handkerchiefs, umbrellas, and others. Per the host’s request, the performance time is day or night. 2) Gamad dance art still exists in the community. 3) The community preserves the Mukomuko Gamad dance art, inviting its dance group to various events.